COLLABORATIVE RESEARCH WORKSHOP PROVIDES OPPORTUNITY FOR COOPERATION TO FOUR UNIVERSITIES - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
KUBANG KERIAN, 29 July 2015 – Workshop on Collaborative Research, held for two days at the Dewan Utama of the Health Campus, Universiti Sains Malaysia (USM) has provided an avenue for research collaborations among four universities situated on the East Coast of Malaysia.